Influence of shortwave laser therapy on morphometric parameters of sciatic nerve regeneration after experimental neurorrhaphy - Z. M. Yashchуshуn; O. O. Dyadyk (Zaporozhye State Medical University, 2023)
The aim of this work was to reveal the effectiveness of delayed laser therapy for the regeneration of the sciatic nerve. Materials and methods. In 21 rats, transection and epineural microsurgical suture of the right sciatic nerve (SN) were performed. In 16 rats (experimental group) in the period from 1.0 to 2.5 months after surgery, a course of laser therapy (LT-1, n = 8) and a delayed (after 6 months) course of laser therapy (LT-2, n = 8) were used 18 sessions were performed in each subgroup. Laser therapy was not performed in 5 operated animals and they were included in the control group. The terms of withdrawal of rats from the experiment were 2.5 and 12.0 months after the operation. During the morphometry of semi-thin sections distal to the level of the sutures, the volumetric density of the constituent elements of the SN, the number density of myelinated nerve fibers (MNF), their diameters, the thickness of the axons and myelin sheath, the myelination index (index G) distribution of MNF by diameter and dependence of index G on the fiber caliber were measured. For double control, we used muscle morphometry data from intact rats (Intact). Muscle tissue was additionally examined by the method of transmission electron microscopy using a generally accepted technique with a REM-100 electron microscope (Selmi, Sumy, Ukraine). Results. In the control group, as compared to the intact group, the numerical density of muscle fibers was 21 % higher, but 38 % less than the numerical density of microvessels, therefore, the vascularization index was reduced by 1.7 times. The obtained results indicated laser compensation for denervation atrophy, which was confirmed by morphometric data. Conclusions. The results of the study indicate a stimulating prolonged effect of delayed laser therapy in regenerative axonogenesis.